2013
DOI: 10.1155/2013/757628
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolic Extract of Polish Propolis: Chemical Composition and TRAIL-R2 Death Receptor Targeting Apoptotic Activity against Prostate Cancer Cells

Abstract: Propolis possesses chemopreventive properties through direct anticancer and indirect immunomodulatory activities. Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) plays a significant role in immunosurveillance and defense against cancer cells. TRAIL triggers apoptosis upon binding to TRAIL-R1 (DR4) and TRAIL-R2 (DR5) death receptors expressed on cancer cell surface. The activation of TRAIL apoptotic signaling is considered an attractive option for cancer prevention. However, as more tumor cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…All the examined acids were previously identified in propolis samples collected from Poland and other European countries, for example Greece, Slovenia, or Italy. 2,14,16,17,19,30 The chemical composition of Polish propolis extracts prepared in 70% and 96% ethanol suggests that aqueous ethanol is a better solvent for extraction of phenolic compounds, especially flavonoids from raw propolis, which was confirmed by statistical analysis. Mavri et al 2 stated that propolis extract obtained using 70% ethanol as the extraction solvent contained higher amounts of flavonoids and phenolic acids than the propolis extract prepared by extracting the material with 96% ethanol.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…All the examined acids were previously identified in propolis samples collected from Poland and other European countries, for example Greece, Slovenia, or Italy. 2,14,16,17,19,30 The chemical composition of Polish propolis extracts prepared in 70% and 96% ethanol suggests that aqueous ethanol is a better solvent for extraction of phenolic compounds, especially flavonoids from raw propolis, which was confirmed by statistical analysis. Mavri et al 2 stated that propolis extract obtained using 70% ethanol as the extraction solvent contained higher amounts of flavonoids and phenolic acids than the propolis extract prepared by extracting the material with 96% ethanol.…”
mentioning
confidence: 78%
“…28,29 High concentrations, especially in EEP70, were also recorded for galangin, chrysin, apigenin, and kaempferol, previously reported in propolis samples collected from various regions of Poland. 14,16,19,30 The concentration of apigenin and kaempferol in both examined extracts was higher than in propolis extracts from Italy, Spain, and China. 28,29 The concentration of chrysin in Italian propolis extracts (4.38-4.56 mg/mL) was higher than in EEP96 and comparable to concentration in EEP70.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Activation of death receptors (DRs) such as tumor necrosis factor receptor 1 (TNFR1), FAS (TNFRSF6) and the TNF-related apoptosis-inducing ligand (TRAIL) receptors, TRAIL-R1 (DR4) and TRAIL-R2 (DR5) is important for anticancer effects of chemotherapeutics Szliszka et al 2013). An activated DR triggers activation of caspases, including caspases-3, 8 and-9, as well as the increase of Bax and decrease of Bcl-2 (Kantari and Walczak 2011;Kaufmann et al 2012;Yin 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of studies demonstrated that propolis reveals substantial properties, including the promotion of soft tissues healing and regeneration/reparation. Apart from its antibacterial [1][2][3][4][5][6], anti-inflammatory [7,8], antioxidant [9][10][11], immunoprotective [12], hepatoprotective activities [13,14], propolis has also anti-proliferative [15][16][17][18][19] and proapoptotic ones [20][21][22][23]. Composition of propolis is diverse and depends on both place of origin and time in which it has been collected.…”
mentioning
confidence: 99%